Facilitators and leadership styles: theoretical drivers for performance budgeting adoption in Iraq’s higher education sector - Khudhair, Ali Hussein; Daud, Zaidi Mat; Abdul Razak Mustafa, Hasri; Al-Zubaidi, Ali Naeem Jasim (Cogent OA, 2025)
This study investigates the adoption of performance-based budgeting (PBB) in Iraq’s Ministry of Higher Education and Scientific Research (MOHE), addressing challenges in aligning budgeting practices with performance outcomes. Motivated by gaps in the literature on public sector budget reforms, particularly in Iraq and other developing countries, the study surveys 317 MOHE employees. It employs partial least squares structural equation modelling to analyze internal and external factors and the moderating roles of transactional and servant leadership styles. The findings reveal that transactional leadership significantly enhances PBB facilitation, while servant leadership has an indirect effect, emphasizing the need for a balanced leadership approach. By contributing to contingency theory, the study highlights the critical role of facilitators in PBB implementation and aligns with global public sector budgeting reforms. These results provide strategic insights for higher education administrators and policymakers, particularly in contexts with centralized governance and limited financial autonomy. Despite focusing on Iraq’s higher education sector, the insights may have implications for other developing nations facing similar challenges and suggest avenues for future research, including qualitative studies to explore these dynamics further.